Original articleImpact of L-DOPA treatment of patients with Parkinson’s disease on mononuclear subsets and phagocytosis in the peripheral blood - Hurny, Artur; Michałowska-Wender, Grażyna; Wender, Mieczysław (Folia Neuropathologica, 2013)
Until now, the question as to the role of immunological mechanisms in neuronal death of extrapyramidal cell systems in Parkinson’s disease (PD) has not been fully resolved. One of the approaches includes examination of circulating blood cells. In our studies on 24 PD patients, peripheral blood was studied before and after medication with L-DOPA compounds. Patients with PD demonstrated an increase in lymphocyte CD95/CD3 ratio as well as a considerable number of cells dead due to apoptotic processes. After treatment with L-DOPA, both the CD95/CD3 ratio, assumed to represent an antigen marker characteristic of apoptotic cells, and the number of cells dead due to apoptotic processes were found to be decreased. Thus, the findings indicate that levodopa treatment in PD has an impact on apoptotic processes and this should be taken into consideration as a positive event in the pathomechanism precipitated by this treatment.